Biochemical properties of lactic acid bacteria for efficient silage production: an update - Akhtar, Muhammad Faheem; Wenqiong, Chai; Umar, Muhammad; Changfa, Wang (Frontiers in Microbiology, 2025)
Ensiling, a microbial-driven process employed for preserving fresh forage in both bio-refineries and animal production, triggers significant biochemical transformations. These changes have spurred the exploration of novel silage additives, with a particular emphasis on the potential of microbial strains that exhibit superior biopreservation capabilities. Lactic acid bacteria (LAB) species have gained widespread recognition for their diverse applications as additives in the fermentation of crops and forage biomasses during ensiling. Nonetheless, recent variations in silage quality might be attributed to a lack of comprehensive information on the gene expression and molecular mechanisms of the microbiota involved in silage production. Contemporary research efforts have been directed toward uncovering nutrient-rich animal feed solutions through enhanced LAB inoculants. This review aims to shed light on the role of LAB inoculants in silage production and the modern biotechnological methods, including metabolomics, proteomics, metagenomics, genomics, transcriptomics, and genetic manipulation. These powerful tools are instrumental in the identification, enhancement, and development of high-performance LAB strains. Additionally, the review outlines emerging trends and prospective developments in LAB advancement for the enhancement of silage, which holds significant promise for breakthroughs in sustainable agriculture and improved animal feed production.